Causes of Medication Errors in Inpatient Wards at Private Hospital in Malang - Faruqi, Faris; Maiga Mahliafa Noor, Viva; Suryanto, Suryanto (Fakultas Kedokteran Universitas Brawijaya, 2022)
The absence of medication errors is a sign of successful implementation of patient safety management, particularly safe treatment. The quality indicator data report at the Pharmacy Installation of a private hospital in Malang in 2020 showed a number of drug administration errors in the inpatient unit. This study aimed to explore the incidence and causes of medication errors in the inpatient unit. The study was conducted at a private hospital in Malang in August-September 2021. The study design was descriptive with data collected through focus group discussions (FGD) with five inpatient pharmacy staff, four inpatient nurses, and the head of the medical support. The study results indicated no clear regulation, especially the Standard Operational Procedure (SOP) for administering drugs to inpatients, which becomes a latent cause of medication errors. Hospitals need to develop SOPs for administering drugs to inpatients according to the 7 Pillars, followed by socialization to nurses in inpatients and periodic monitoring.